Qaumī taʻlīm o tarbiyyat : Sar Sayyid ke nuq̤tah-yi naẓar se - Farzānah Begam (Āminah Ḵẖātūn], 1978)
On the educational ideologies of the Muslim social reformer and educator Sir Syed Ahmad Khan, 1817-1898.